Effect of Psychological Empowerment on Employee Job Satisfaction of Nepalese Commercial Banks - Shah, Shruti (Nepalese Journal of Finance, 2024)
This study examines the effect of psychological empowerment on employee job satisfaction of Nepalese commercial banks. Employee job satisfaction is the dependent variable. The selected independent variables are psychological empowerment, meaningful work, organizational commitment, employee performance and self-determination. The primary source of data is used to assess the opinions of the respondents regarding psychological empowerment, meaningful work, organizational commitment, employee performance and self-determination in Nepalese commercial banks. The study is based on primary data with 121 respondents. To achieve the purpose of the study, structured questionnaire is prepared. The correlation coefficients and regression models are estimated to test the significance and importance of different factors affecting employee job satisfaction in Nepalese commercial banks.The study showed that psychological empowerment has a positive impact on employee job satisfaction. It implies that providing psychological empowerment leads to employee job satisfactions. Likewise, meaningful work has a positive impact on employee job satisfaction. This indicates that assigning employees with meaningful work leads to the employee job satisfactions. Similarly, organizational commitment has a positive impact on employee job satisfaction. It indicates that the organizational commitment towards employees enhance employee job satisfaction. Moreover, employee performance has a positive impact on employee job satisfaction indicating that better performance in job leads to the employee job satisfaction. Likewise, self-determination has a positive impact on employee job satisfaction which indicates that higher the level of self-determination in employees, higher would be the satisfaction from the job.